"Dynamics of India-Middle East Relations: A Comprehensive Exploration" (International Journal of Food and Nutritional Sciences, 2022)
The paper explores the multifaceted and evolving relationship between India and the Middle East, examining the historical, political, economic, and strategic dimensions. Over the decades, the interaction between India and Middle Eastern nations has grown in significance, encompassing diplomatic ties, economic cooperation, and shared regional concerns. The paper delves into the historical context of this relationship, highlighting key milestones, diplomatic engagements, and mutual influences. It analyzes the role of India as a key player in the Middle East's economic landscape, discussing trade, energy, and investment collaborations. Additionally, the paper examines the strategic dimensions of the relationship, encompassing security concerns, counter- terrorism cooperation, and geopolitical alignments. Drawing on a comprehensive array of primary and secondary sources, including diplomatic archives, academic analyses, and official statements, this paper provides a nuanced understanding of the dynamic and evolving ties between India and the Middle East.